Pembaharuan Hukum Penanganan Tindak Pidana Korupsi oleh Korporasi Melalui Pengaturan Illicit Enrichment dalam Sistem Hukum Nasional - Ana Fauzia; Fathul Hamdani (Jurnal Hukum Lex Generalis, 2022)
In this time, the motives or concept of corruption are increasingly complex and growing, as well as the increasing number of transnational crimes, makes the world need regulations regarding Illicit Enrichment in legal products at the level of law to allow the imposition of legal sanctions for these crimes, including Indonesia. The purpose of this study is to provide an overview of the practice of Illicit Enrichment in several countries in the world and the urgency of its regulation in Indonesia, as well as an analysis of the construction of legal reforms in handling corruption by corporations through the regulation of Illicit Enrichment in the national legal system. From the results of the study, through this regulation related to Illicit Enrichment, it can prevent public officials (corporations) from committing corruption, minimizing initiatives to do business or other activities that are full of conflicts of interest (with their positions). Furthermore, the formulation of the idea of constructing Illicit Enrichment arrangements in this study is divided into three, namely: the formulation of the subject, the formulation of the offense, and the formulation of sanctions and asset confiscation. Through this Illicit Enrichment setting, asset pursuit or tracing can be further maximized. In addition, criminal provisions, especially related to Illicit Enrichment/unexplained wealth are urgently needed and considered urgent because the Anti-Corruption Law has not fully implemented/regulated the provisions of Illicit Enrichment as an independent criminal offense. Illicit Enrichment is applied to the "accused", not from the beginning of the investigation or investigation process (suspect), but only as a reinforcement of existing evidence for corruption crimes committed.